2015
DOI: 10.5897/ajpp2014.4180
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic properties of Melissa officinalis and associated mechanisms of action: A review of the literature

Abstract: The anxiety disorders prevalence has significantly increased in society. These disorders can be treated with anxiolytics which, despite great efficacy, may result in several adverse side effects. Several studies have reported that anxiolytic effects result from the indirect action on the GABAergic system and mechanisms related to the cholinergic system. Melissa officinalis has been widely utilized for its sedative action and its ability to reduce agitation. Several studies using this plant in different experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…(Eivan, et al;2020). Melissa also displaces the (3H) (N)-escopolaminica, (3-H-N) nicotinic and M receptors by increasing the acetylcholine (Ach) following nerve stimulation which might improve cognitive function (Barbara, et al;.There is a dependency risk too which is associated with lemon balm which is due to its tolerance build up in longer administration (Barbara, et al;.There has been several recordings of the usage of Melissa officinalis in sedation. Several recent studies have confirmed the anxiolytic profile of Melissa officinalis.…”
Section: Anxiolytic Activitymentioning
confidence: 99%
“…(Eivan, et al;2020). Melissa also displaces the (3H) (N)-escopolaminica, (3-H-N) nicotinic and M receptors by increasing the acetylcholine (Ach) following nerve stimulation which might improve cognitive function (Barbara, et al;.There is a dependency risk too which is associated with lemon balm which is due to its tolerance build up in longer administration (Barbara, et al;.There has been several recordings of the usage of Melissa officinalis in sedation. Several recent studies have confirmed the anxiolytic profile of Melissa officinalis.…”
Section: Anxiolytic Activitymentioning
confidence: 99%